2012
DOI: 10.1007/s10681-012-0685-1
|View full text |Cite
|
Sign up to set email alerts
|

Early generation selection at multiple locations may identify potato parents that produce more widely adapted progeny

Abstract: Potato production in the eastern United States occurs over a wide range of environments from Maine to Florida; many of these states do not have a breeding program. Initial selections are usually made at the breeding location for more than 2 years before undergoing evaluation elsewhere, at which point, few clones remain from the original population. The purpose of this study was to determine if parents that produce progeny with broad adaptation could be identified early in the USDA/ARS Potato Breeding Program. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
0
12
2
1
Order By: Relevance
“…Thirty-seven (16.3%) of these were selected in both FL 2015 and ME 2015. The percentages for selected clones between ME and FL were higher than an earlier study (9.7%) looking at early generation selection in tetraploid clones undergoing evaluation for more traditional markets (Haynes et al, 2012). FL and ME 2015 both agreed to discard 70 clones (30.8%), which was lower than in the previously mentioned study where 55.5% of the clones were discarded (Haynes et al, 2012).…”
Section: Mecontrasting
confidence: 75%
See 1 more Smart Citation
“…Thirty-seven (16.3%) of these were selected in both FL 2015 and ME 2015. The percentages for selected clones between ME and FL were higher than an earlier study (9.7%) looking at early generation selection in tetraploid clones undergoing evaluation for more traditional markets (Haynes et al, 2012). FL and ME 2015 both agreed to discard 70 clones (30.8%), which was lower than in the previously mentioned study where 55.5% of the clones were discarded (Haynes et al, 2012).…”
Section: Mecontrasting
confidence: 75%
“…The percentages for selected clones between ME and FL were higher than an earlier study (9.7%) looking at early generation selection in tetraploid clones undergoing evaluation for more traditional markets (Haynes et al, 2012). FL and ME 2015 both agreed to discard 70 clones (30.8%), which was lower than in the previously mentioned study where 55.5% of the clones were discarded (Haynes et al, 2012). FL and ME 2015 disagreed on the fate of the remaining 120 clones (52.9%), which was higher than in the previously mentioned study where they disagreed on 34.8% of the clones.…”
Section: Mecontrasting
confidence: 73%
“…Cross prediction based on progeny mean has also been practised for tuber blight and foliage blight (Caligari et al 1983) as well as potato cyst nematodes Globodera pallida (Phillips 1981). Haynes et al (2012) studied if parents that produce progeny with broad adaptation could be identified early in a potato breeding programme. For this seed of all second field generation clones were distributed to five locations for selection.…”
Section: Progeny Testmentioning
confidence: 99%
“…Seed dormancy in potatoes, has been positively correlated with tuber dormancy (Simmonds, 1964). So, the quality seed (TPS) can not only be related to final yields, but might also affect seed tuber quality (Barrington, 1971) [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%